Framing Reputation: Public Communication Strategies of The Bureau of Communication and Information Services in Strengthening Public Trust in The Ministry of Finance - Supriyanto Supriyanto (Balai Diklat Keagamaan Bandung, 2026)
Public communication plays a vital role in shaping organizational reputation and fostering public trust in government institutions. In an increasingly dynamic media environment, news framing by mass media and social media can significantly influence public perceptions of institutional credibility. As the public relations unit of Indonesia’s Ministry of Finance, the Bureau of Communication and Information Services (KLI) serves as a strategic intermediary between the institution and the public, particularly in responding to issues and negative publicity that may affect organizational reputation. This study aims to examine and analyze the communication strategies employed by the KLI Bureau to maintain and strengthen the Ministry’s reputation in both current and future contexts. Using a qualitative approach, data were collected through focus group discussions and in-depth interviews and analyzed using thematic analysis. The findings reveal that reputation management constitutes the primary focus of public communication within the Ministry of Finance. The KLI Bureau promotes a positive organizational reputation through integrated communication strategies, including the use of social media and collaboration with Key Opinion Leaders (KOLs). Crisis management is carried out proactively by monitoring issues and responding quickly to negative sentiment. The study also identifies several challenges, including internal coordination, limited communication competencies, and the need to adapt technical messages to diverse audiences. To enhance communication effectiveness, the study recommends optimizing KOL engagement, strengthening positive institutional narratives, and improving organizational capacity through training and coordination.